Representasi Ideologi Media Sosial dan Netizen Indonesia pada Film Budi Pekerti (2023) - Almas Aqil Gusni Rahmana; Ike Desi Florina; Didi Permadi (Universitas Medan Area, 2026)
The phenomenon of social media has given birth to a new culture in social life, where digital public opinion often plays the role of moral controller. This study analyzes the representation of Indonesian social media and netizens in the film Budi Pekerti (2023) by Wregas Bhanuteja using Teun A. van Dijk's Critical Discourse Analysis approach. This research aims to reveal how the ideology of social media and Indonesian netizens is represented in ethical films. The results of the study show that in the text dimension, films depict the distortion of meaning and public judgment in the digital space as a form of instant morality ideology. In the dimension of social cognition, it displays ideological awareness of netizens' culture that is reactive and loses empathy. Meanwhile, in the context dimension, it reflects the condition of Indonesian people who live in the hegemony of social media, where image is more important than humanity.